Effects of Dose and Injection Site on Gingival Smile Treatment with Botulinum Toxin Type A: A Prospective Study. Issue 1 (7th October 2022) - Gong, Xi; Yuan, Mengning; Gu, Chenyang; Yan, Boxi; Li, Jianjun; Zou, Lidong; An, Yang; Tang, Zhihui; Han, Xuefeng
Abstract : Background: Botulinum toxin type A is an easy and efficacious treatment for gingival smile. However, the optimal dose and injection site are controversial. The authors compared the reduction in gingival exposure using two methods with different doses and injection sites. Methods: In this prospective self-controlled study, healthy participants with gingival smile (anterior gingival exposure of >3 mm) underwent two treatment methods. First, participants received a single-point injection of 2 U of botulinum toxin type A per side (simplified method). After 8 months, the individualized method was performed with 2 to 5 U of botulinum toxin type A (total, 4 to 10 U), which was injected at one or two sites according to pretreatment severity. Data were collected at baseline and at 4, 12, and 32 weeks of follow-up. Results: Fifty-five participants were enrolled. Anterior gingival exposure and bilateral posterior gingival exposure were significantly reduced 4 and 12 weeks after botulinum toxin type A injection ( P ≤ 0.05) with both methods. These parameters returned to baseline by 32 weeks ( P > 0.05). Posttreatment anterior gingival exposure at 4 weeks and 12 weeks with the individualized method was significantly lower compared with the simplified method (both P ≤ 0.05). Patient satisfaction with the individualized method was preferred compared with the simplified method ( P ≤ 0.05). Few adverse events were observed with both methods without statistical significance. Conclusion: It is necessary to increase the injection dose and tailor the injection site according to the pretreatment severity of anterior gingival smile.